Usage of excess heat for district heating - Analysis of enabling factors and barriers. (20th August 2022) - Fritz, Markus; Savin, Margaux; Aydemir, Ali
Abstract: The use of industrial excess heat can be an important factor for the expansion and decarbonization of district heating networks. However, the enabling factors and barriers to implement excess heat recovery projects for district heating are still uncertain. Here, drivers and barriers for the integration of excess heat into district heating networks are analysed and a public available database of 45 implemented projects in Germany, Austria and France is created. 5 hypotheses of enabling factors and barriers were formulated and tested through 13 expert interviews with excess heat producers. Unlike the current literature, expert interviews are combined with a literature review to test the hypotheses. Thus, both quantitative and qualitative data are used to verify or refute the hypotheses. The results demonstrate that projects are often implemented only thanks to individuals and that the communication and exchange between the necessary stakeholders is often insufficient. It is also evident here that relevant stakeholders are often unaware of excess heat recovery opportunities. Furthermore, the results show that financial aspects are often not the main reasons for excess heat recovery for district heating, but play an important role in the decision-making. In conclusion, there are many barriers that can be overcome through meaningful policy design or better information and support.